Historical Notices of the ’Broch’ or Burghead, in Moray, with an Account of its Antiquties - MacDonald, James (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author briefly describes the geographical and architectural features of the town of Burghead in Moray, before summarising the written accounts from medieval and contemporary sources that may refer to the history of this area. He highlights that most of the historical references to the town were related to the history of Scandinavians in Scotland until Major-General Roy’s second map of the Highlands, in which he suggests that the town was originally a Roman settlement.